The importance of language and literary art in reading suppressed voices and voices in transition in selected Zimbabwean fiction - Hungwe, Elda (2017)
The paper examines how literature and linguistics are inextricably linked. It reflects how literature uses language to expose the dynamic relations between men and women in the land discourse between men and women in Vera's Nehanda, Hoba's 'The Trek' and Nyamubaya's On The Road Again. Since one of the major functions of language is to communicate, Vera speaks through her writing/fiction that patriarchal notions can be superseded by an ultimate authority thus she invokes spirituality to create the female agency, thus an uncontested platform that is acknowledged by men. Hoba provides a voice through young male generation. Nyamubaya on the other hand uses poetry with a conscious voice to speak on behalf of women.